(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The term Prior Learning Assessment (PLA) is used globally, but different countries and institutions use various terms to describe the recognition of prior learning (RPL) and the assessment of skills acquired outside traditional educational settings. This document provides some common terms used worldwide.